BEACH RESOURCES STUDY FOR ECOTOURISM ADJUSTMENT AT TEMAJUK BEACH TEMAJUKVILLAGE PALOH DISTRICT SAMBAS REGENCY - juliatno, juliatno juliatno; Ahmad Mulyadi, Ahmad Mulyadi Ahmad Mulyadi; Inpurwanto, Inpurwanto Inpurwanto (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACT This study aims to determine the coastal tourism potential seen from the perceptions and social characteristics of the community and visitors as well as knowing the ecological suitability of the coastal area with the carrying capacity of the Temajuk Beach area. The research was carried out from July-December 2018 at the Temajuk Beach area of Temajuk Village, Paloh District, Sambas Regency. The method used in this study is primary data collection of water quality analysis, method of determining regional suitability based on the multiplication of scores and weights obtained from each parameter, depth, beach type, beach width, water brightness, current velocity, water base material, biota observation dangerous, and availability of clean water. Based on the results of research at Temajuk Beach, it has natural resource potential that can be developed into a coastal ecotourism area. Beach tourism activities that can be done in this area include swimming, sunbathing, water sports and beach recreation. The Regional Suitability Index (IKW) in Temajuk Beach area Temajuk village, Paloh sub-district is categorized very according to the percentage of each station. At station one which is at Tanjung Bendera Beach with a percentage of 88.57% and station two which is on Mauludin Beach with a percentage of 87.85%. The carrying capacity of the area in Temajuk Beach is 160 people / day for swimming, sunbathing, beach recreation and water sports. Keywords: Ecotourism, Potential, Beaches, Social Perceptions